EPIDEMIOLOGICAL PROFILE OF THE MASTOLOGY CLINIC IN A UNIVERSITY HOSPITAL IN THE NORTHWEST OF PARANÁ - Ito, Edgar Junji; Safar, Antonio Soares (Mastology, 2017)
Introduction: W ith i ncreased a wareness a bout b reast c ancer, d iscovering a b reast l ump c an c ause e motional s tress i n p atients. Thus, diagnostic methods are used to distinguish and confirm benign and malignant breast pathologies. Objective: To characterize the epidemiological profile of the Mastology Clinic of the University Hospital of Maringá, in a period of one year, defining the incidence of benign and malignant breast diseases in patients undergoing breast cancer screenings in the local public health network. Methods: A cross-sectional, retrospective and descriptive study, with data collection from patients seen at the Mastology Clinic from March 2015 to February 2016. Results: Of the 103 patients, 99% were female, 82.3% were between 40 and 69 years old, and 80.5% were white. Regarding the patient’s main complaint, 55% had only one altered imaging exam, 7% had only clinical complaints, and 32% had a palpable nodule in addition to an altered imaging exam. The main findings in the imaging exams were nodules, present in 67.1% of mammograms and 80% of mammographic ultrasonography, with inconclusive or suspected classification in 77.9% of mammograms and 65.7% of ultrasonography. Biopsies were performed in 71.8% of the patients. Benign pathologies corresponded to 76.1% of the diagnoses and 25 cases of breast cancer were identified. Conclusion: The epidemiological profile of the Clinic presented similar characteristics to the literature during the period studied. Referrals to specialists were justified because the changes in the imaging exams warranted further investigation. Diagnostic procedures fulfilled their role, differentiating and confirming benign and malignant breast diseases.